Prenatal Gentle Yoga Combination with Dhikr on Sleep Quality Among Pregnant Women In Rural And Urban Areas - Nurhidayah, Nurhidayah; Nurul Fadhilah Gani; Hasnah (Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction: Sleep is physiological process for physical and mental health in pregnant women. However, it is a common problem, and very important to overcome. Limitation of chemical drugs is an important basis for developing non-pharmacological interventions in overcoming sleep disorders in pregnant women. Exercise with prenatal Gentle Yoga And Dhikr is needed to improve sleep quality. This study aim to determine the effect of Prenatal Gentle Yoga And Dhikr ton sleep quality among pregnant women in Rural and Urban areas. Methods: This study was quantitative research with quasy experimental (non equivalent group) design. The research conducted at Bajeng primary health centre (rural area) and Kassi-Kassi Primary Health Centre (urban area). There were 30 pregnant women who were participants in this study were selected using a purposive sampling technique. Data were analized using SPSS ver 26 program with friedman test for determine effectivity of intervention, and general linier model to determine differences between rural and urban groups. Results: The results showed that there was an effect of prenatal gentle yoga and dhikr in improve sleep quality in pregnant women in rural and urban areas p (0.000). There is a difference in the effectiveness of prenatal gentle yoga and dhikr in rural and ruban areas p (0.007). This intervention was more effective in urban than rural areas. Conclusions: Prenatal Gentle yoga with dhikr is an effective interventions to improve sleep quality for pregnant women in rural and urban areas. For this reason, it is hoped that this intervention will become an option for maternal physical exercise during pregnancy. . Keywords: Prenatal Gentle Yoga, Sleep Quality, Pregnant Women